(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2025)
This essay analyzes the importance of episteme and epistemology as critical frameworks for understanding and mitigating environmental damage, overcoming the reductionist and technocratic approaches that have historically dominated environmental science. It argues that the current ecological crisis is not solely the result of extractive practices and inadequate policies, but also of epistemic structures that legitimize certain forms of knowledge while rendering others such as local and ancestral knowledge invisible. The central objective is to demonstrate that integrating a plural and reflexive epistemology is an essential condition for developing fairer, more democratic, and sustainable environmental policies and practices. Through a critical approach, the essay contends that knowledge production is mediated by historical, political, and cultural contexts that define which impacts are considered relevant and how they are managed. In conclusion, the essay proposes an epistemological transformation that integrates science, ethics, and society as the foundation for addressing the global ecological crisis.